Vaginal Flora Alterations and Clinical Symptoms in Low-Risk Pregnant Women - Gondo, Fausto [UNESP]; Silva, Marcia da [UNESP]; Polettini, Jossimara [UNESP]; Tristao, Andrea da R. [UNESP]; Peraçoli, José Carlos [UNESP]; Witkin, Steven Sol [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Karger, 2011)
Background: To evaluate associations between alterations in vaginal flora and clinical symptoms in low-risk pregnant women. Methods: Vaginal specimens from 245 pregnant women were analyzed by microscopy for vaginal flora. Signs and symptoms of vaginal infection were determined by patient interviews and gynecologic examinations. Results: Abnormal vaginal flora was identified in 45.7% of the subjects. The final clinical diagnoses were bacterial vaginosis (21.6%), vaginal candidosis (10.2%), intermediate vaginal flora (5.2%), aerobic vaginitis (2.9%), mixed flora (2.9%) and other abnormal findings (2.9%). The percentage of women with or without clinical signs or symptoms was not significantly different between these categories. The presence of vaginal odor or vaginal discharge characteristics was not diagnostic of any specific flora alteration; pruritus was highly associated with candidosis (p < 0.0001). Compared to women with normal flora, pruritus was more prevalent in women with candidosis (p < 0.0001), while vaginal odor was associated with bacterial vaginosis (p = 0.0026). Conclusion: The prevalence of atypical vaginal flora is common in our low-risk pregnant population and is not always associated with pathology. The occurrence of specific signs or symptoms does not always discriminate between women with different types of atypical vaginal flora or between those with abnormal and normal vaginal flora. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Vaginal flora; Bacterial vaginosis; Candidosis; Aerobic vaginitis; Vaginal symptoms; Pregnancy